Scalable Hybrid Switching-Driven Software Defined Networking Issue : From the Perspective of Reinforcement Learning Standpoint - Blose, Max; Akinyemi, Lateef Adesola; Ojo, Stephen; Faheem, Muhammad; Imoize, Agbotiname Lucky; Khan, Arfat Ahmad (IEEE, 2024)
The Software-Defined Networking technology promises to enhance network performance and cost reduction for service providers by providing scalability, flexibility, and programmability through the separation of the control plane from the data plane. However, the separation between the control plane and data plane in the implementation of SDN presents scalability issues, as the controller has limited computational resources. To address the SDN scalability issues identified, we create a scalable hybrid switching solution using machine learning algorithms. We propose an SDN OpenFlow model switch which collaborates with the traditional switch to represent a scalable framework of Hybrid Routing with Reinforcement Learning (sHRRL). We implement a reinforcement algorithm to randomly explore new routes and discover the most optimal path through the Q-learning algorithm. This primitive and model-free form of reinforcement learning utilizes the Markov Decision Process and Bellman’s equation to reiteratively update Q-values in the Q-table for every transition in the network environment state until Q-function has converged to the best Q-values. The proposed hybrid switching model is benchmarked against the standard SDN OpenFlow switch in terms of network performance metrics, including throughput, packet exchange transmission rates, CPU load, and delay. When statistically comparing simulation results, it is evident that the proposed switching model, incorporating machine learning algorithms, can effectively tackle scalability challenges in the design of SDN controller networks, especially in Data Centre environments where rapid switching speeds are crucial.
Keywords: Controller; data centre; hybrid switching; OpenFlow; scalability; SDN; sHRRL; Control systems; Routing; Protocols; Routing protocols; Software defined networking; Switching systems; machine learning; protocols (data communications); fi=Tietotekniikka|en=Computer Science|